Quantização de partículas com spin - Tilles, P. F. C [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Aclassical relativistic particleis described by means of Dirac's formalism for constrained systems, where the constraints come from the reparametrization invariance required by an explicitly covariant theory. We introduce spin degrees of freedom via Grassman variables, which leads directly to the concept of supersymmetry in the theory. The equations of motion and quantization are considered both for the spin 0 and 1/2 free theories, and for the eletromagnetic interaction. The ﬁrst class constraints algebra is extended to describe spin N/2 particles, which include spin 1 representations. The quantum theory obtained is compared to the classical theory of ﬁelds

Uma partícula clássica relativística é descrita utilizando-se o formalismo de Dirac para sistemas vinculados devido à invariança sob transformações de reparametrizações requerida por uma teoria explícitamente covariante. Nós introduzimos os graus de liberdade de spin via variáveis de Grassman, que levam diretamente ao conceito de supersimetria presente na teoria. As equações de movimento e a quantização são consideradas tanto para as teorias livres de spin 0 e 1/2, como para a teoria com interação eletromagnética. A álgebra dos vínculos de primeira classe é extendida para descrever partículas de spin N/2, que incluem as representações de spin 1. A teoria quântica obtida é comparada com a teoria clássica de campos
Keywords: Partículas (Física nuclear); Particles (Nuclear physics)